Constructing a feminist desistance: resisting responsibilization - Barr, Úna (Feminist responses to injustices of the state and its institutions, 2024)
Criminology’s focus on desistance theory is illustrative of its phallocentric occupation. This chapter considers the implications of this wilful acceptance in criminal justice policy and practice on the experiences of criminalized women while considering an alternative anti-carceral, intersectional feminist way forward. First, the drive of desistance praxis which has perpetually encouraged criminalized women to (re)enter and engage with ‘conventional society’ and develop and maintain social bonds that will support desistance trajectories is critiqued. It is argued that ‘re/integration’ is often not possible, nor desired. Second, it is contended that a concentration on agentic, individualized desistance, as well as uncritical promotion of relational desistance, has resulted in state support for responsiblized criminalized individuals making changes to their own lives, in the absence of robust structural support mechanisms. Finally, it is outlined how the bulk of desistance literature has not critiqued the role of the prison, nor the wider aspects of the criminal justice system in creating social harm, beyond contributing to, or standing as a barrier to, desistance from crime. The chapter is concluded by putting forward a vision for anti-carceral, intersectional feminist desistance research, theory, policy and practice.